2018
DOI: 10.1111/tbed.13073
|View full text |Cite
|
Sign up to set email alerts
|

First detection of novel enterovirus G recombining a torovirus papain‐like protease gene associated with diarrhoea in swine in South Korea

Abstract: Enterovirus species G (EV‐G) comprises a highly diversity of 20 genotypes that is prevalent in pig populations, with or without diarrhoea. In the present study, a novel EV‐G strain (KOR/KNU‐1811/2018) that resulted from cross‐order recombination was discovered in diagnostic faecal samples from neonatal pigs with diarrhoea that were negative for swine enteric coronaviruses and rotavirus. The recombinant EV‐G genome possessed an exogenous 594‐nucleotide (198‐amino acid) sequence, flanked by two viral 3Cpro cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…Interestingly, 2019-To-4 contained an extra 657 nt sequence within the 2C–3A junction region. This sequence showed homology to the PL-CP sequence variant that was recently found in EV-G1, G2 and G17 strains isolated in the USA, Belgium, Japan, China and Korea [15–21]. Standard similarity plot analysis in SimPlot software v.3.5.1 with the 2019-To-4 sequence as a separate query revealed that 2019-To-4 had a higher sequence similarity to EV-Gs carrying a PL-CP sequence (PL-CP EV-Gs) than to EV-G strains without a PL-CP in the non-structural protein regions ().…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Interestingly, 2019-To-4 contained an extra 657 nt sequence within the 2C–3A junction region. This sequence showed homology to the PL-CP sequence variant that was recently found in EV-G1, G2 and G17 strains isolated in the USA, Belgium, Japan, China and Korea [15–21]. Standard similarity plot analysis in SimPlot software v.3.5.1 with the 2019-To-4 sequence as a separate query revealed that 2019-To-4 had a higher sequence similarity to EV-Gs carrying a PL-CP sequence (PL-CP EV-Gs) than to EV-G strains without a PL-CP in the non-structural protein regions ().…”
Section: Resultsmentioning
confidence: 69%
“…The role of EV-Gs as diarrhoea-causing enteric pathogens is still unclear [14]. However, recently, recombinant EV-Gs carrying a papain-like cysteine protease (PL-CP) sequence of torovirus, a member of the order Nidovirales , in the 2C/3A junction site of their genome were identified in the faecal samples of pigs with diarrhoea in the USA, Belgium, China, South Korea, Germany and Japan [8, 15–21]. The PL-CP sequence encodes a deubiquitinase/delSGylase that potentially improves the ability of a virus to evade host immunity, resulting in diarrhoea in neonatal pigs [16].…”
Section: Introductionmentioning
confidence: 99%
“…PToV is regarded as a swine diarrhea virus that has not caused huge economic losses [ 25 ]. However, given the high recombination rate and evolutionary characteristics of coronavirus and torovirus, we cannot underestimate their potential threat [ 28 30 ]. It is very likely that a virulent strain could emerge and cause unpredictable damage to the pig industry [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains to be a potential pathogen in pigs [25][26][27]. It should be noted that frequent recombination events involving PToV have been discovered, some of which, especially those on the Hemagglutinin-esterases (HE) or Spike (S) genes, which encode proteins relating to attachment and invasion, could lead to changes in pathogenicity or host-specificity [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Their HE, which is related to haemagglutinin-esterase-fusion (HEF) protein of influenza C, and PDE are thought to have been independently obtained from these ancestors by heterologous recombination events ( Figure 2 ) [ 92 ]. Remarkably, heterologous recombination between ToV and picornavirus has been discovered recently in many countries; a ToV-like PL pro gene is inserted into the porcine enterovirus G (EV-G) genome at the 2C/3A junction [ 93 , 94 , 95 , 96 , 97 ] or completely replaces a viral structural gene up to the VP1/2A junction [ 98 , 99 ] ( Figure 3 c), suggesting that ToV-like PL pro benefits the growth of EV-G.…”
Section: Genomementioning
confidence: 99%